Application of a Coupled Eulerian-Lagrangian Approach to the Shape and Force of Scientific Balloons - Lingsen Kong; Yanchu Yang; Rong Cai; Hangyue Zhang; Weihao Lyu (Applied Sciences)
Scientific balloons provide an inexpensive and reliable platform for near-space scientific experiments. The analysis of the balloon geometry and forces has always been a major concern for balloon designers. Most previous studies have focused solely on the fully inflated shapes and forces of balloons, analyzing only the membrane structure and simplifying the effects of internal and external gases into a gradient pressure difference. This approach lacks consideration of the fluid–structure interaction (FSI) of scientific balloons. This paper utilizes the Coupled Eulerian–Lagrangian (CEL) method in the Abaqus/Explicit simulation environment to analyze the FSI effects of scientific balloons under the influence of internal helium and external air. Three typical working conditions of scientific balloons are selected for simulation analysis. First, a three-dimensional spherical balloon is simulated during the ascent process to verify the correctness of the CEL simulation framework. This also demonstrates the membrane folding characteristics during balloon ascent, which could not be calculated in previous two-dimensional axisymmetric simulations. Next, the study explores balloon shapes that deviate from quasi-static pressure distributions due to the motion of internal helium. These include the “mushroom” shape observed during the dynamic launching of the balloon on the ground and the “sail” shape caused by lateral airflow. The mushroom shape arises from the sudden loss of the bottom constraint, causing the internal helium to move upward while being resisted by the air at the balloon’s top. The simulation successfully replicates the rapid waist transition and the downward concavity at the top due to air resistance, while also providing the corresponding force distribution. For the sail-shaped condition, the simulation analyzes the balloon’s tilt angle and the characteristic upturn of its windward surface. By a comparison with no-wind conditions, this study quantifies the impact of wind on the forces acting on the balloon, offering practical guidance for balloon launching. The CEL simulation framework established in this study not only provides a new tool for the FSI analysis of scientific balloons but also enriches the mechanical analysis results of these balloons.